Pars Plana Vitrectomy and Heavy Silicon oil Tamponade for Inferior Retinal Detachment - Murat Aslankurt; Mustafa Kurt; Burak Erden; Mustafa Nuri Elçioğlu; Osman Çekiç (Türk Oftalmoloji Dergisi, 2012)
Pur po se: To evaluate the effectiveness and safety of pars plan vitrectomy and heavy silicone oil tamponade in eyes with inferior retinal detachment. Ma te ri al and Met hod: Eighteen eyes that underwent pars plana vitrectomy and heavy silicone oil (Densiron) tamponade were evaluated retrospectively. Twenty-gauge vitrectomy was performed and heavy silicon oil was introduced at the conclusion of the surgery. Patients were examined postoperatively at 1 day, 1 week, and monthly intervals. Silicon was removed in suitable eyes during the study period. Best-corrected visual acuity, ocular tension measurements, and biomicroscopic examinations were performed. Final visual and anatomic results were recorded. Re sults: The median age of the patients was 43 (range: 16-67) years. Associate ocular pathology to the inferior detachments were dropped nucleus (n=2), complicated uveitis (n=1), degenerative myopia (n=2), penetrating trauma (n=2), and blunt ocular trauma (n=3). Eight (44%) eyes had previous unsuccessful detachment surgery. Anatomic success was achieved in 16 (88%) eyes at a mean of 11.76 months (range: 5- 21) of follow-up. Visual acuity was improved in 4 eyes, stabilized in 12 eyes, and worsened in 2 eyes. Postoperative hypotony developed in one eye, and oil emulsification developed in 2 eyes. Dis cus si on: Use of heavy silicone oil (Densiron) tamponade is effective and safe in eyes with inferior retinal detachment. (Turk J Ophthalmol 2012; 42: 458-61)